2010
DOI: 10.1111/j.1365-3113.2010.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and biogeography of Thyridosmylus (Neuroptera: Osmylidae)

Abstract: The first phylogenetic analysis of the genus Thyridosmylus Krüger is presented. All species from China were scored in a morphological analysis, along with extralimital species from India (Thyridosmylus pustulatus Kimmins) and Madagascar (Thyridosmylus marmoratus Fraser), and were compared with out-group exemplars from Spilosmylus Kolbe, Thaumatosmylus Krüger and Osmylus Latreille. A monophyletic Thyridosmylus sister to Spilosmylus is confirmed based on this analysis, with the Malagasy Thyridosmylus marmoratus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…6), the structure of the female sclerites is also variable among subfamilies. The enlarged gonocoxite 9 (=gonopophyses lateralis) is closely associated anteriorly with gonopophysis 9 (=sternite 9 of Wang et al (2011)) in Protosmylinae, Spilosmylinae and Osmylinae and two separate sclerites are clearly visible. By contrast, in more derived subfamilies Porisminae, Kempyninae, Eidoporisminae and Stenosmylinae, gonopophyses 9 is not closely associated as a regular sclerite with gonocoxite 9, but instead is more elaborately shaped as a single articulating sclerite which acts upon sternite 8.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…6), the structure of the female sclerites is also variable among subfamilies. The enlarged gonocoxite 9 (=gonopophyses lateralis) is closely associated anteriorly with gonopophysis 9 (=sternite 9 of Wang et al (2011)) in Protosmylinae, Spilosmylinae and Osmylinae and two separate sclerites are clearly visible. By contrast, in more derived subfamilies Porisminae, Kempyninae, Eidoporisminae and Stenosmylinae, gonopophyses 9 is not closely associated as a regular sclerite with gonocoxite 9, but instead is more elaborately shaped as a single articulating sclerite which acts upon sternite 8.…”
Section: Methodsmentioning
confidence: 97%
“…Terminology follows Tjeder (1957), Adams (1969) and Wang et al (2011) with the following modifications based of detailed examinations and a recent assessment of structural homology across all genera of Osmylidae and related families of Neuroptera (SLW, unpublished data). Figure 5 depicts the various male genitalic structures (colour-coded) typically exhibited in Protosmylinae.…”
Section: Methodsmentioning
confidence: 99%
“…The congeneric status of all species in the genus has been routinely accepted by subsequent authors (Wang et al 2008, 2011; Winterton et al 2017); in a cladistics analysis of Thyridosmylus , Wang et al (2011) concluded the Malagasy species occupy a sister position to the Oriental species, suggesting the southern origin of this genus should be no later than Late Cretaceous. Indeed, in their phylogenetic analyses of Osmylidae, Winterton et al (2017) deduced that the divergence of Thyridosmylus from its sister genus Spilosmylus Kolbe occurred during the Middle Jurassic (177 Mya), and that early splits in both genera were caused by vicariance resulting from the subsequent rafting of India.…”
Section: Introductionmentioning
confidence: 99%
“…Presently there are 19 species described in Thyridosmylus , including 17 species from South East Asia and two from Madagascar, suggesting the conspicuously disjunct geographical distribution (Gerstaecker 1884; Navás 1933; Kimmins 1942; Fraser 1955; Yang 1987, 1988, 1992, 1993, 1999, 2002; Yang et al 1995; Wang et al 2008, 2011). The congeneric status of all species in the genus has been routinely accepted by subsequent authors (Wang et al 2008, 2011; Winterton et al 2017); in a cladistics analysis of Thyridosmylus , Wang et al (2011) concluded the Malagasy species occupy a sister position to the Oriental species, suggesting the southern origin of this genus should be no later than Late Cretaceous.…”
Section: Introductionmentioning
confidence: 99%
“…A close relationship between Protosmylinae and Spilosmylinae is supported by molecular data and by the presence of unique features in male and female genitalia, in particular the presence of a narrowly arching gonarcus (Winterton and Wang 2016; Winterton et al 2017). Spilosmylinae are recognizable due to the presence in the hind wing of a spur vein originating basal to the MP vein and of a basal sclerotised process on the mediuncus (Wang et al 2011; Winterton et al 2017). This group is by far the largest subfamily of osmylids, with at least 113 described species, although placed in only three genera: Thaumatosmylus Krüger (8 species), Thyridosmylus Krüger (20 species) and the most diverse genus of the family, Spilosmylus Kolbe (85 species).…”
Section: Introductionmentioning
confidence: 99%